Efficacy of smear layer removal at apical third of root canal by different irrigation regimens using XP-endo Shaper: an in vitro SEM study - Varma, K Madhu; Mavidi, Jagapathi Babu; Satish, R Kalyan; Indukuri, Sai Lakshmi; Manishaa, Bondada; Gadde, Praveen (International Journal of Dental Materials, 2024)
Background: Effective root canal therapy relies heavily on irrigation, as it is the sole method capable of reaching the internal anatomy of the root canal that remains inaccessible with mechanical instrumentation. Aim: To compare the efficacy of different irrigation regimes on smear layer removal with XP-endo Shaper at the apical third of the root canal in lower premolars under a scanning electron microscope. Materials and methods: Forty-four human single-rooted lower premolars were collected and decoronated to a standard length. Teeth were categorized into four groups based on the irrigation regimes: distilled water (DW Group), 5.25% NaOCl and 17% EDTA (SE Group), super-oxidised water and 17% EDTA (SPO Group), TWIN KLEEN solution (TK Group). Scanning electron microscopic evaluation was done at 3 mm from the apex to analyse the remaining amount of smear layer. Kruskal-Wallis test and Mann–Whitney U test were employed in this study. Results: On comparing the ability of four different irrigation regimes to remove the smear layer, the SPO and SE Groups showed significantly higher smear layer removal (p<0.05) in the apical third of the root canal system than the TK and DW Groups. Conclusion: In conclusion, the use of sodium hypochlorite or super-oxidised water throughout and post-instrumentation followed by chelator (EDTA) was found to be more efficient compared to a combination of NaOCl and HEBP solution in smear layer removal in the apical third instrumented with XP-endo Shaper.